Analisis Strategi Bersaing di PT. Citra Van Titipan Kilat (Tiki) - , Ignasia Reni Wiyasti; , Dr. Wakhid Slamet Ciptono, MBA., MPM., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Competition is a challenge that must be faced by every firm in maintaining business continuity in an effort to maintain the survival of the company. Competition arises because the development of the business and environmental changes that continue to occur. Tiki strives to continue to grow in the competitive business delivery services. The company's goal can be achieved if the company's competitive advantage can be appropriately and in accordance with the characteristics of the product and the target market. Companies should strive to provide delivery services to customers very quickly and accurately so that the service is one of the most influential factors to be a superior company. Even companies must follow current developments in technology and the demands of increasingly high service users. The purpose of this study is to analyze the business strategy adopted by PT. TIKI in overcoming competition express delivery services industry and identifies the key success factors PT. TIKI industry to face competition. The data in this study were analyzed qualitatively, the secondary data in the form of the theory, the definition and substance of the literature, as well as primary data collected from the interviews was analyzed using analysis of the value chain, five forces competitive and VRIO order to get business strategies adopted Tiki and factors PT-key success factors. Tiki. Based on the analysis, it is concluded that the PT. Tiki is a competitor in the industry is very diverse including freight companies both locally and internationally and via air or via land. Therefore, the numbers of competitors are not equal in size and strength. Companies that had stood since long had a competitive advantage in terms of economies of scale that can compete in terms of price and restrict incoming threats. After seeing the key to success and competence held by the company, the strategy used by the PT. Tiki is a low-cost strategy, especially in the organization, operations, marketing and distribution costs by opening a franchise system. Low-cost strategy is the most important way to win business competition. However, PT. Tiki also implements differentiation strategies as reflected in the company's activities advantages compared to other competitors.